Preparation method and application of foamy copper loaded Co3CuN anti-perovskite material

By using foamed copper-supported Co3CuN anti-perovskite materials in the field of water treatment, the existing heterogeneous Fenton catalysts have been solved, and efficient and stable catalytic effects and low-cost preparation process have been achieved.

CN119565650AActive Publication Date: 2025-03-07HOHAI UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411702504.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-07
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The existing heterogeneous Fenton catalysts have poor stability, complex preparation process and high cost, which limit their wide application in the field of water treatment.

Method used

Foam copper is used as the copper source and substrate, cobalt hexahydrate as the cobalt source, and urea as the inducer, and foam copper-loaded Co3CuN anti-perovskite material is synthesized by hydrothermal method and high-temperature nitriding and reduction one-step method.

Benefits of technology

The synthesis steps are simplified, the cost is reduced, the structural stability and catalytic activity of the material are improved, and the problems of poor stability and complex preparation of traditional catalysts are overcome.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565650A_ABST
    Figure CN119565650A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a foamy copper loaded Co3CuN anti-perovskite material. In-situ formation of a Cu / Co hydroxide precursor is promoted by taking cobalt nitrate hexahydrate as a cobalt source, foamy copper as a copper source and a substrate and urea as an inducer; high-temperature nitridation and reduction adopt a one-step method, NH3 is generated through decomposition of urea at high temperature, and reduction and nitrogen doping of the metal material are achieved. Meanwhile, the net structure of the foamy copper provides abundant sites for loading the Co3CuN on the foamy copper. Co3CuN grown on foamy copper in situ is stable in structure, metal ions are effectively prevented from being separated out, the dispersity of the material is improved, and metal-nitrogen coupling in anti-perovskite further improves the catalytic activity of the material. The catalyst disclosed by the invention can generate singlet oxygen with high selectivity after being in contact with potassium hydrogen persulfate, new pollutants in a water body can be efficiently and quickly removed by virtue of high oxidability and specificity of the singlet oxygen, and the catalyst has the potential to become a Fenton-like catalyst with excellent performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental protection and water treatment, and specifically relates to a preparation method and application of a foam copper-loaded Co3CuN anti-perovskite material. Background Art

[0002] With the development of human industrial technology and the improvement of people's living standards, many emerging pollutants have quietly emerged and quickly occupied every corner of human society. These emerging pollutants are called new pollutants in my country, including persistent organic pollutants, endocrine disruptors, antibiotics, etc. The main source of new pollutants is the production and use of toxic and harmful chemicals. Their characteristics are that they are exposed unknowingly, will remain for a long time, and are not easy to detect harm to human health and environmental systems. Because of their low concentration but high toxicity, complex and stable chemical structure, the common treatment technologies in the field of water treatment, including physical treatment, chemical treatment, biological treatment, and membrane separation treatment, are not effective in treating new pollutants. Advanced oxidation technology degrades pollutants through the oxidation of highly active free radicals, and is suitable for treating new pollutants that are difficult to remove with traditional treatment technologies. Fenton oxidation is a process that uses hydrogen peroxide (H2O2) and divalent iron ions (Fe 2 + ) produces hydroxyl radicals (·OH), thereby oxidizing and degrading pollutants in water. The Fenton-like process is an advanced oxidation technology modified on the basis of the Fenton process. Compared with the Fenton process, the Fenton-like process reaction uses different metal ions (such as Fe 3+ , Cu 2+ , Mn 2+ etc.) to generate highly active free radicals (such as hydroxyl radicals OH) and non-free radicals (such as singlet oxygen 1 O2) to degrade the difficult-to-degrade pollutants in water.

[0003] In advanced oxidation technologies such as the Fenton process, it is common to use heterogeneous catalysts to activate oxidants. Heterogeneous catalysts refer to catalysts that exist in solid form and are in different phases (such as solid-liquid or solid-gas) from the reactants. Common heterogeneous Fenton-type catalysts include iron-based oxides, composite oxides, iron-based materials loaded with iron, molecular sieves and metal organic frameworks (MOFs). In addition, heterogeneous catalysts loaded with catalysts on stable materials have also been widely studied. Compared with homogeneous catalysts (such as Fe 2+ or Fe 3+), heterogeneous catalysts have the advantages of easy separation, recyclability, low residual metal pollution, and a wider operating range. The above advantages of heterogeneous catalysts make them applicable in solid, liquid, and gas fields. In the field of water treatment, they are used to remove trace pollutants in drinking water and difficult-to-degrade organic matter in wastewater, and are especially suitable for deep treatment of high-concentration wastewater; in soil remediation, solid heterogeneous catalysts can be directly applied to soil remediation, using water and H2O2 in the soil to achieve in-situ oxidative degradation; in air treatment systems, heterogeneous catalysts can be used in combination with ozone or H2O2 to degrade volatile organic matter in the air. However, heterogeneous catalysts also have disadvantages: since the catalyst is in a solid state and cannot fully contact the solution, its activity may not be as good as that of homogeneous catalysts; after multiple cycles, the catalyst surface may be covered by pollutants or by-products, resulting in catalyst deactivation; heterogeneous catalysts often contain metal elements such as iron, copper, and manganese. Under acidic or extreme conditions, these metals are easily dissolved, resulting in secondary pollution, especially in Fenton-type catalysts, where the leaching of Fe ions will pollute the effluent water; the synthesis steps are complex and costly, and the preparation process of some heterogeneous catalysts requires precise control of temperature, pressure, atmosphere and other conditions. The complex synthesis process limits the large-scale production and application promotion of catalysts; in a dynamic water flow environment, catalyst particles may be lost with the water flow, and the lost catalyst not only affects the treatment efficiency, but also increases the particle pollution of the water body. Although heterogeneous catalysts have many advantages in the field of water treatment, their low catalytic activity, easy deactivation, metal leaching and difficulty in regeneration limit their wide application. In order to improve the application prospects of heterogeneous catalysts, it is necessary to develop more stable, easily recyclable and widely applicable heterogeneous catalysts, while exploring simpler regeneration methods and low-cost synthesis processes to overcome the current shortcomings and limitations.

[0004] Antiperovskites are formed by the inversion of perovskite electrons. They have magnetism, superconductivity, negative thermal expansion, and the ability to act as photoluminescent host materials. They can also change magnetic properties, transport channels, and catalytic properties by adjusting the composition of the antiperovskite lattice and fine-tuning the metal-nitrogen coupling. The performance of the metal-nitride active centers of these antiperovskites is comparable to that of metal ions, so that antiperovskites have catalytic activity similar to that of metal ions and avoid secondary pollution caused by the precipitation of metal ions during the reaction. In recent years, various antiperovskites such as Cu3N and Co4N have been synthesized and have achieved good results in the degradation of pollutants. They are promising new heterogeneous catalysts. However, the synthesis process of antiperovskites is complicated and the powdered materials are difficult to recover. For example, Cu3N requires the solution to be continuously degassed in nitrogen at 105°C for 1h, and then the temperature of the reaction mixture is raised to 260°C for 5min, and then cooled to 80°C. After that, the particles are centrifuged at 7000rpm and dried. Therefore, simplifying the synthesis steps and enhancing recyclability are top priorities for expanding the application of antiperovskites in advanced oxidation technologies. Summary of the invention

[0005] In view of the problems faced by existing heterogeneous Fenton-type catalysts, such as poor stability, complex preparation process and high cost, the present invention provides a preparation method and application of a copper foam-loaded Co3CuN antiperovskite material, using cobalt nitrate hexahydrate as a cobalt source, copper foam as a copper source and substrate, and urea as an inducer, and adopting a hydrothermal method, high-temperature nitridation and reduction one-step synthesis. The preparation method is simple and low in cost. The copper foam-loaded Co3CuN antiperovskite material has a stable structure and has good application prospects.

[0006] In order to solve the existing technology, the technical solution adopted by the present invention is:

[0007] A method for preparing a copper foam-loaded Co3CuN antiperovskite material, using cobalt nitrate hexahydrate as a cobalt source, copper foam as a copper source and a substrate, and urea as an inducer to promote the in-situ formation of a Cu / Co hydroxide precursor; then a high-temperature nitridation and reduction one-step method is used to decompose urea at high temperature to produce NH3, thereby achieving simultaneous reduction and nitrogen doping of the precursor to form a copper foam-loaded Co3CuN antiperovskite material.

[0008] As an improvement, the above preparation method comprises the following steps:

[0009] Step 1, dissolving metal salt and urea in pure water and stirring them fully to obtain a mixed solution;

[0010] Step 2, activating the copper foam;

[0011] Step 3, transferring the mixed solution and the treated copper foam to a stainless steel high-pressure reactor lined with polytetrafluoroethylene for hydrothermal reaction to obtain a Cu / Co hydroxide precursor;

[0012] Step 4, wash the Cu / Co hydroxide precursor 2-3 times, vacuum dry it, and then place it in a small porcelain boat A and spread it evenly. Then place the small porcelain boat A in a tube furnace, and place a small porcelain boat B with sufficient urea in front. Then, in a high temperature and N2 atmosphere, urea is decomposed into NH3, and the Cu / Co hydroxide precursor is subjected to high-temperature nitridation and reduction under the action of NH3 to obtain a foam copper-loaded antiperovskite material.

[0013] A further improvement is that the metal salt in step 1 is Co(NO3)2·6H2O, and the concentration is 50mM-80mM; the concentration of urea is 267mM-533mM.

[0014] As a further improvement, in step 1, the concentration of Co(NO3)2·6H2O is 50 mM and the concentration of urea is 267 mM.

[0015] Further improvement is that the density of the copper foam in step 2 is 800-1500g / m 3 , the area is 6×10 -4 m 2 .

[0016] A further improvement is that the pretreatment in step 2 is to use acetone, 0.1 mol / L hydrochloric acid, and anhydrous ethanol to ultrasonically immerse the foam copper, respectively, and the ultrasonic time is 5-10 minutes. Before changing the immersion liquid, the foam copper is taken out and rinsed from top to bottom with ultrapure water. The washing process is repeated 3 times.

[0017] A further improvement is that in step 3, the hydrothermal reaction temperature is 100-150°C and the hydrothermal reaction time is 5-8h.

[0018] As a further improvement, in step 4, the vacuum drying temperature is 50-70°C, and the vacuum drying time is 10-12h; the high temperature nitriding temperature is 500-700°C, and the time is 2-5h.

[0019] The above-mentioned application of the foam copper loaded Co3CuN anti-perovskite material in the degradation of new pollutants, wherein the new pollutants are tetracycline hydrochloride, sulfamethoxazole or ciprofloxacin.

[0020] Beneficial effects:

[0021] The preparation method and application of a foam copper-loaded Co3CuN antiperovskite material of the present invention have the following advantages:

[0022] 1. The present invention adopts an in-situ generation method for preparation, specifically using cobalt nitrate hexahydrate as a cobalt source, copper foam as a copper source and substrate, urea as an inducing agent, and adopting a hydrothermal method, high-temperature nitridation and reduction one-step synthesis. The target catalyst can be synthesized by only two operations, simplifying the synthesis steps. It solves the problem that common loading methods such as solvent thermal method and impregnation method have loose bonding between the substrate and the catalyst, which easily causes the loss of the catalyst and leads to secondary pollution.

[0023] 2. The present invention uses copper foam as a copper source and substrate. The mesh structure of copper foam provides abundant sites for the in-situ generation of Co3CuN, making its structure stable, effectively preventing metal ions from precipitating and improving the dispersibility of Co3CuN antiperovskite materials. The in-situ growth method forms a strong chemical bond between the antiperovskite catalyst and the copper foam substrate, increases the stability of the catalyst, reduces the problem of falling off during use, and the presence of nitrogen in the antiperovskite and the metal-nitrogen coupling improve the catalytic activity of the catalyst. Therefore, the copper foam loaded Co3CuN antiperovskite has both a stable material structure and an efficient catalytic activity, overcoming the problems of poor stability, complex preparation process and high cost faced by heterogeneous Fenton-like metal catalysts, and is a promising new heterogeneous catalyst.

[0024] 3. The presence of nitrogen in the antiperovskite of the present invention and the metal-nitrogen coupling synergistically improve the catalytic activity of the foam copper-loaded Co3CuN antiperovskite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 XRD patterns of the Co3CuN antiperovskite materials supported by copper foam prepared at different high-temperature nitridation temperatures;

[0026] Figure 2 This is a graph showing the degradation rate of different pollutants using the material foam copper loaded with Co3CuN prepared in Example 1;

[0027] Figure 3 This is a graph showing the degradation rate of sulfamethoxazole with a concentration of 20 mg / L cyclically degraded by using the material foam copper loaded with Co3CuN prepared in Example 1;

[0028] Figure 4 This is a graph showing the degradation rate of sulfamethoxazole with a concentration of 20 mg / L after 20 minutes of ultrasonic treatment using the copper foam loaded Co3CuN prepared in Example 1. DETAILED DESCRIPTION

[0029] The technical scheme of the present invention is further described in detail below through embodiments, but the content of the present invention is not limited thereto, and the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, without departing from the essence of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] The methods in this example are all conventional methods unless otherwise specified, and the materials, reagents, etc. used are all obtained from commercial channels or prepared according to conventional methods unless otherwise specified.

[0031] Example 1

[0032] A method for preparing a foam copper-loaded Co3CuN antiperovskite material comprises the following steps:

[0033] S1. Solution mixing

[0034] 50 mM Co(NO3)2·6H2O and 267 mM urea were stirred for 10 min to obtain a mixed solution;

[0035] S2. Activation treatment of copper foam

[0036] The density of the purchased 3 The copper foam was cut into a size of 2×3 cm, and then ultrasonically soaked in acetone, 0.1 mol / L hydrochloric acid, and anhydrous ethanol for 10 min. When the soaking liquid was changed, the copper foam was rinsed from top to bottom with ultrapure water. The washing process was repeated 3 times to obtain activated copper foam.

[0037] S3. Hydrothermal reaction

[0038] The mixed solution and the treated copper foam were transferred to a stainless steel autoclave lined with polytetrafluoroethylene and maintained at 120°C for 6 h to obtain a Cu / Co hydroxide precursor;

[0039] S4, high temperature nitriding

[0040] The Cu / Co hydroxide precursor was washed with ultrapure water, and the washing process was repeated 3 times. Then, it was vacuum dried at 60°C for 12 hours. Then, the Cu / Co hydroxide precursor was spread evenly and loaded into a small porcelain boat A. The small porcelain boat A was placed in a tube furnace, and a small porcelain boat B with sufficient urea was placed in front. At 550°C and in a N2 atmosphere, urea was decomposed into NH3. The precursor was subjected to high-temperature nitridation and reduction under the action of NH3 to obtain an antiperovskite Co3CuN material loaded on copper foam, which was recorded as Co3CuN-550.

[0041] Example 2

[0042] Except that the high temperature nitridation temperature in step 3 is changed to 800° C., the rest is the same as in Example 1, and the obtained catalyst is recorded as Co3CuN-800.

[0043] Figure 1 This is the XRD diagram of the materials prepared in Examples 1-2. It can be seen from the figure that all diffraction peaks of the product Co3CuN-550 of Example 1 and the product Co3CuN-800 of Example 2 are completely consistent with the typical Co cals and Cu cals, which indicates that Co3CuN was successfully synthesized.

[0044] Example 3

[0045] Experimental test on degradation of new pollutants by the material prepared in Example 1:

[0046] Prepare 20mg / L tetracycline hydrochloride, sulfamethoxazole, and ciprofloxacin solutions with a volume of 100mL, and adjust the solution to neutrality with dilute sulfuric acid and sodium hydroxide solution. Add the prepared catalyst 2×3cm to the solution, stir mechanically, and then add potassium persulfate to make the potassium persulfate concentration in the system 0.65mM. Set the temperature to 25℃, and measure the change of pollutant concentration over time after adding potassium persulfate.

[0047] The effect of copper foam loaded Co3CuN antiperovskite material in degrading various pollutants, the results are as follows Figure 2 The copper foam loaded anti-perovskite has good degradation performance for tetracycline hydrochloride, sulfamethoxazole and ciprofloxacin. The degradation rates of tetracycline hydrochloride, sulfamethoxazole and ciprofloxacin within 600s are 100%, 100% and 89%, respectively.

[0048] Example 4

[0049] Experimental test on the catalytic cycle of the material prepared in Example 1:

[0050] Prepare a 20mg / L sulfamethoxazole solution with a volume of 100mL, and adjust the solution to neutrality with dilute sulfuric acid and sodium hydroxide solution. Add 2×3cm of the prepared catalyst to the solution, stir mechanically, and then add potassium persulfate to make the concentration of potassium persulfate in the system 0.65mM. Set the temperature to 25℃ and the reaction time to 10min. After the reaction is completed, remove the catalyst sheet from the solution and rinse it from top to bottom three times with anhydrous ethanol and pure water respectively. Re-configure 100mL of deionized water solution, add the washed catalyst to the solution, stir mechanically, and then add potassium persulfate to make the concentration of potassium persulfate in the system 0.65mM. Set the temperature to 25℃ and the reaction time to 10min. Repeat this 4 times.

[0051] Depend on Figure 3 It can be seen that the copper foam loaded Co3CuN antiperovskite provided by the present invention degrades sulfamethoxazole by activating potassium persulfate, and the first cycle achieves 100% degradation within 10 minutes, and after 5 cycles, the degradation rate is still 100%, which proves that the copper foam loaded Co3CuN antiperovskite prepared by the present invention has good cycle performance.

[0052] Example 5

[0053] Experimental test on the stability of the material prepared in Example 1:

[0054] Prepare a 20 mg / L sulfamethoxazole solution with a volume of 100 mL, and adjust the solution to neutrality with dilute sulfuric acid and sodium hydroxide solution. First, put the prepared catalyst 2×3 cm into an ultrasonic device for 20 minutes, then add it to the solution, stir it mechanically, and then add potassium persulfate to make the potassium persulfate concentration in the system 0.65 mM. Set the temperature to 25°C, and measure the change of pollutant concentration over time after adding potassium persulfate.

[0055] The effect of copper foam loaded with antiperovskite in the degradation of pollutants, the results are as follows Figure 4 As shown, the degradation performance of copper foam loaded antiperovskite on sulfamethoxazole can still reach 100% within 10 minutes, which proves that the structure of copper foam loaded Co3CuN antiperovskite is stable.

[0056] In summary, the copper foam loaded anti-perovskite material prepared by the present invention has a simple preparation method, low cost, and the characteristics of high catalytic activity and high stability, and therefore has the potential to become a Fenton-like catalyst.

[0057] The present invention and its embodiments are described schematically above, and the description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. Therefore, if a person skilled in the art is inspired by it and designs a structural method and an embodiment similar to the technical solution without creativity without departing from the purpose of the invention, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a foam copper-loaded Co3CuN antiperovskite material, characterized in that: The preparation method uses cobalt nitrate hexahydrate as a cobalt source, copper foam as a copper source and substrate, and urea as an inducer to promote the in-situ formation of a Cu / Co hydroxide precursor; then a high-temperature nitridation and reduction one-step method is used to decompose urea at high temperature to produce NH3, thereby achieving simultaneous reduction and nitrogen doping of the precursor to form a copper foam-loaded Co3CuN antiperovskite material.

2. The method for preparing a foam copper-loaded Co3CuN antiperovskite material according to claim 1, characterized in that: The following steps are involved: Step 1, dissolving metal salt and urea in pure water and stirring them fully to obtain a mixed solution; Step 2, activating the copper foam; Step 3, transferring the mixed solution and the treated copper foam to a stainless steel high-pressure reactor lined with polytetrafluoroethylene for hydrothermal reaction to obtain a Cu / Co hydroxide precursor; Step 4, wash the Cu / Co hydroxide precursor 2-3 times, vacuum dry it, and then place it in a small porcelain boat A and spread it evenly. Then place the small porcelain boat A in a tube furnace, and place a small porcelain boat B with sufficient urea in front. Then, in a high temperature and N2 atmosphere, urea is decomposed into NH3, and the Cu / Co hydroxide precursor is subjected to high-temperature nitridation and reduction under the action of NH3 to obtain a foam copper-loaded Co3CuN antiperovskite material.

3. The method for preparing a foam copper-loaded Co3CuN antiperovskite material according to claim 2, characterized in that: The metal salt in step 1 is cobalt nitrate hexahydrate (Co(NO3)2·6H2O) with a concentration of 50mM-80mM; the concentration of urea is 267mM-533mM.

4. The method for preparing a foam copper-loaded Co3CuN antiperovskite material according to claim 3, characterized in that: In step 1, the concentration of Co(NO3)2·6H2O is 50 mM and the concentration of urea is 267 mM.

5. The method for preparing a foam copper-loaded Co3CuN antiperovskite material according to claim 2, characterized in that: The density of the copper foam in step 2 is 800-1500g / m 3 , the area is 6×10 -4 m 2 .

6. The method for preparing a foam copper-loaded Co3CuN antiperovskite material according to claim 2, characterized in that: The pretreatment in step 2 is to use acetone, 0.1 mol / L hydrochloric acid, and anhydrous ethanol to ultrasonically immerse the foam copper for 5-10 minutes, take out the foam copper before changing the immersion liquid, and rinse the foam copper from top to bottom with ultrapure water. The washing process is repeated 3 times.

7. The method for preparing a foam copper-loaded Co3CuN antiperovskite material according to claim 2, characterized in that: In step 3, the hydrothermal reaction temperature is 100-150° C., and the hydrothermal reaction time is 5-8 h.

8. The method for preparing a foam copper-loaded Co3CuN antiperovskite material according to claim 2, characterized in that: The vacuum drying temperature in step 4 is 50-70 o C, vacuum drying time is 10-12 h; high temperature nitriding temperature is 500-700 o C, time is 2-5 h.

9. Application of the foam copper-loaded Co3CuN antiperovskite material prepared by the preparation method according to any one of claims 1 to 8 in the degradation of new pollutants, characterized in that: The new pollutant is tetracycline hydrochloride, sulfamethoxazole or ciprofloxacin.

Citation Information

Patent Citations

  • Anti-perovskite phase nitride three-dimensional self-supporting electrode material for reducing nitrate to prepare ammonia and preparation method and application of anti-perovskite phase nitride three-dimensional self-supporting electrode material

    CN114672822A

  • Foamy copper loaded cobalt nitride catalyst, preparation method and application

    CN115323403A